Is da Vinci Xi Better than da Vinci Si in Robotic Rectal Cancer Surgery? Comparison of the 2 Generations of da Vinci Systems. Issue 5 (October 2016) - Ozben, Volkan; Cengiz, Turgut B.; Atasoy, Deniz; Bayraktar, Onur; Aghayeva, Afag; Erguner, Ilknur; Baca, Bilgi; Hamzaoglu, Ismail; Karahasanoglu, Tayfun
Abstract : Background: We aimed to compare perioperative outcomes for procedures using the latest generation of da Vinci robot versus its previous version in rectal cancer surgery. Patients and Methods: Fifty-three patients undergoing robotic rectal cancer surgery between January 2010 and March 2015 were included. Patients were classified into 2 groups (Xi, n=28 vs. Si, n=25) and perioperative outcomes were analyzed. Results: The groups had significant differences including operative procedure, hybrid technique and redocking ( P >0.05). In univariate analysis, the Xi group had shorter console times (265.7 vs. 317.1 min, P =0.006) and total operative times (321.6 vs. 360.4 min, P =0.04) and higher number of lymph nodes harvested (27.5 vs. 17.0, P =0.008). In multivariate analysis, Xi robot was associated with a shorter console time (odds ratio: 0.09, P =0.004) with no significant differences regarding other outcomes. Conclusions: Both generations of da Vinci robot led to similar short-term outcomes in rectal cancer surgery, but the Xi robot allowed shorter console times.